Analisis Pengungkapan Informasi Akuntansi terhadap Bias Investor dalam Menafsirkan Akrual - Aulia, Norliyani (AL-QARDH, 2020)
In an investment activity can sometimes cause errors in the process of perceiving information related to investment. This is caused by bias so that it can cause market anomalies. Perception bias is a person